Study on EMC of High Power Photovoltaic Grid-connected Inverter - WU Hengliang; JIAN Fang; TANG Haiyan (Kongzhi Yu Xinxi Jishu)
It mainly introduced the topology of photovoltaic grid-connected inverter, analyzed the electromagnetic problems of high power photovoltaic grid-connected inverter, and proposed some solutions. The experimental results indicate that the proposed solutions are feasible, and the inverter EMC has good performance and running stability.